Customer orientation: The interactive effect of role clarity and learning goal orientation - Templer KJ; Kennedy JC; Phang R (Emerald Publishing Limited)
Purpose Customer orientation of service employees relates to customer satisfaction and loyalty, sales growth and business performance. Drawing from conservation of resources (COR) theory, the aim of this study was to test the interactive effects of service employees' role clarity and learning goal orientation on customer orientation. Specifically, it was hypothesized that even under conditions of low role clarity, service employees with high learning goal orientation would maintain a high level of customer orientation. Design/methodology/approach Participants were 323 employees of 4- and 5-star hotels in Singapore. Using questionnaires, they reported their role clarity, learning goal orientation and customer orientation. For hypothesis testing, moderated regression analysis was performed. Findings Role clarity and learning goal orientation were significantly related to customer orientation, and in support of the hypothesis, the interaction effect of role clarity and learning goal orientation was also significant. With high role clarity, all employees showed high customer orientation. But with low role clarity, only employees with high learning goal orientation demonstrated high customer orientation. Practical implications The recommendations from this study are to include learning goal orientation as a selection criterion for service employees and to clearly define the roles of existing service employees, especially for those with low learning goal orientation. Originality/value The originality and value of this study lies in highlighting the importance of learning goal orientation especially under conditions of low role clarity.
Keywords: Conservation of resources (COR) theory; Customer orientation; Role clarity; Role ambiguity; Learning goal orientation; Moderated regression analysis